PENGGUNAAN MEDIA SOSIAL YOUTUBE DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SMP AL KARIM RASYID KOTABUMI - Martoyo Martoyo; Silvia Febriyanti (JURNAL ILMIAH NUSANTARA, 2026)
Nowaadays technological advances are increasingly sophisticated, youtube social media asaform of technological innovation that makes it easier to get information designed in the form of audio visuals so that it can be used as a learning medium today. The purpose of this study is to find out the use of youtube social media in increasing students' interest in learning Islamic Religious Education subjects at Al Karim Rasyid Elementary School. This study uses a qualitative research method with a descriptive approach. The subjects of the research consisted of the Principal, teachers of Islamic Religious Education subjects, and 5 students of the third grade of Al Karim Rasyid Elementary School. Data collection techniques through observation, interviews, and documentation. Data analysis techniques are carried out by data reduction, data presentation, conclusion drawing and verification. The results of this study show that the use of youtube social media in increasing students'interest in learning in Islamic Religious Education subjects at Al Karim Rasyid Senior High School is good,through the suitability of the use of youtube asa learning medium combined with the ability of teacher stop provide teaching,able to operate youtube well, which is supported by the availability of facilities so as to provide efficiency in learning in the form of good and fast understanding,as well as many other benefits.In the use of youtube can increase student interest, it can be seen that when learning PAI using youtube students feel happy because of the attractive images and sound sprovided by youtube, student interest increases through different learning atmospheres when learning with youtube, ice breaking, group assignments, giving follow-up assignments, and the selection of short videos makes students focus on paying attention, students become active in asking and answering questions when learning to use youtube.